Course of brittle diabetes: 12 year follow up. Issue 6787 (25th May 1991) - Tattersall, R; Gregory, R; Selby, C; Kerr, D; Heller, S
Abstract : OBJECTIVE–To determine the course of brittle diabetes. DESIGN–12 year follow up of patients identified in 1977-9 as having brittle diabetes; retrospective review of the case notes. SETTING–Nottingham health district. SUBJECTS–25 brittle diabetic patients were identified in 1979-9; 11 (five men) had three or more admissions with ketoacidosis between June 1977 and 1979 and 14 (eight men) had three or more attendances at the accident and emergency department with hypoglycaemia in 1978. Two controls from our diabetic register were matched to each patient for age, sex, and duration of diabetes. MAIN OUTCOME MEASURES–Frequency of ketoacidosis and severe hypoglycaemia in the 12 years after ascertainment; diabetic control and complications in 1988-90; retrospective attribution of the cause of brittleness. RESULTS–Patients with recurrent ketoacidosis had had a median (range) of 28 (8-67) episodes. One man died of a cerebral tumour but five of the surviving nine patients had not been admitted in the past two years, although diabetic control remained poor (median haemoglobin A1 concentration 14%). Seven patients had pure hypoglycaemic brittleness, and five had also had eight or more admissions with ketoacidosis (mixed brittleness). Two died of uraemia within a year after ascertainment and two others in hypoglycaemic coma seven and 12 years later. Brittle diabetes was in most cases related to a specific situation, usually unhappiness at home or school. CONCLUSIONS–Brittle diabetes is often episodic and almost always related to stressful life circumstances. Once the underlying cause is removed it tends to improve. Recurrent hypoglycaemic brittleness of psychological origin has a poor prognosis.